Recent advances in the applications of nanozymes for the efficient detection/removal of organic pollutants: a review. Issue 4 (22nd March 2022) - Liu, Qi; Zhu, Xu; Zhong, Linrui; Zhang, Shoujuan; Luo, Xiaozhe; Liu, Qian; Tang, Lin; Lu, Yue
Abstract : Recent advances in the applications of nanozymes for the efficient detection/removal of organic pollutants. Abstract : Global concern regarding the environmental threat of organic pollutants is growing, which requires the development of efficient and environmentally friendly detection/removal techniques. Biological methods, especially those relying on enzymatic processes, have shown excellent performance in alleviating the environmental problems of organic pollutants. However, natural enzymes have certain limitations and drawbacks, such as strict reaction conditions, poor stability, and high cost. To overcome these issues, nanozymes, i.e., nanomaterials with enzyme-like activities, possessing the advantages of low cost, mass production and high stability, have become popular in recent years. This review focuses on recent advances and challenges in the applications of nanozymes for the efficient detection/removal of organic pollutants. Four typical types of nanozymes including peroxidase-like nanozymes, oxidase-like nanozymes, catalase-like nanozymes and superoxide dismutase-like nanozymes are comprehensively evaluated, especially in terms of their catalytic processes and capacities. Moreover, the mechanisms in the nanozyme-driven processes for the detection/removal of organic pollutants are illustrated. Further, key factors such as size, shape, morphology, pH, temperature and other secondary factors are discussed and the ecological effect of nanozymes is briefly summarized. Finally, future research directions in this field and conclusions are indicated. Overall, this review provides a promising and comprehensive environmental perspective on the latest nanozyme-related techniques in the detection/removal of organic pollutants.